Profile of adverse drug reactions in patients on anti-tubercular drugs in a sub Himalayan rural tertiary care teaching hospital - Sood, Atal; Bansal, Rekha; Sharma, Aradhna; H, Himani; Bhagra, Suruchi; Kansal, Dinesh (International Journal of Research in Medical Sciences, 2016)
Background: Tuberculosis is a major public health problem, with one out of three people in the world are infected with Mycobacterium tuberculosis. The prevalence of MDR TB in India is 2-3% among new cases and 12-17% in reinfection cases. One of the reasons for MDR may be noncompliance to treatment due to adverse drug reactions. The present study was conducted to find out ADRs in patients on antitubercular treatment (ATT) under pharmacovigilance programme of India (PvPI). Methods: This was a retrospective observational study. Data was collected through voluntary reporting by health-care professionals (HCP) in standard IPC-PvPI prescribed suspected ADR reporting form and analyzed for 100 patients on ATT. Causality assessment was done using WHO causality assessment scale. Results: The maximum ADRs were reported in adults with a mean age of 40.79±16.79 years. Males (n=66) outnumbered females (n=34). There were 62% MDR-TB on DOTS-plus regimen, followed by 35% on Cat1 ATT for pulmonary and extrapulmonary tuberculosis cases and XDR-TB accounted for 3% of the total cases. The commonest ADRs in patients on MDR treatment were related to CNS 44 (27.5%), followed by Gastrointestinal system 31 (19%), psychiatric 20 (12.5%) otovestibular 13 (8%) and ophthalmic ADRs being the least in frequency 1 (0.6%). In contrast patients on Cat 1 ATT the ADRs involving Gastrointestinal system 44 (44%) followed by CNS 12 (12%), psychiatric 0% and ADRs related to otovestibular manifestations being the least 1 (1%) frequency. Conclusions: ADRs involving different organ systems were seen in both categories with varied frequency. Adverse drug reactions add to hospitalization expenses, insurance costs and increase in work loss days besides addition to patient suffering and loss of compliance. Prior knowledge can help in better prescriptions and prevent valuable resource loss.